Perilaku Solidaritas Penggemar ARMY (Studi Kasus BTS Meal) - Agatha, Theofillia; Utami, Lusia Savitri Setyo (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The emergence of Korean Pop culture is getting easier for us to access, especially because of technological advances around us. The emergence of boy/girl band groups is the result of K- Pop culture itself. Not a few teenagers who idolize several boy/girl band groups from Korea. This study discusses the solidarity behavior of fans of the South Korean boyband, Bangtan Boys or